Artistic musical conducting [videorecording] - Neuen, Donald; Bonamico, Piero (Choral techniques and methods)
"World-renowned choral conductor and music educator Donald Neuen demystifies the essential elements of communication between performers and conductors in these information-packed videos. The inspirational lectures and demonstrations in Artistic Musical Conducting volumes 1 and 2 can dramatically improve your conducting technique and give you the confidence needed to stand in front of any ensemble and lead it effectively"--Publisher.